KEANEKARAGAMAN JENIS AMFIBI ORDO ANURA DI KAWASAN HUTAN LINDUNG GUNUNG SEMAHUNG KECAMATAN SENGAH TEMILA KABUPATEN LANDAK KALIMANTAN BARAT - Yani, Ahmad; Said, Syafruddin; anto, Eri (Universitas Tanjungpura, 2015)
Amphibians is one of all fauna constituent ecosystems and a part of biodiversity in aquatic habitat, terestrial and arboreal.The research aimed to determine diversity of amphibians species ordo Anura in the Gunung Semahung protected forest areas, Sengah Temila District, Landak Regency, West Borneo. This research has done on Februari 12th 2014 until Februari 30th 2014. The method used in this research is Visual Encounter Survey (VES) that combinated with track system by dividing three lines of aquatic habitats and three lines of terestrial habitats.Â The number of species found were 18 species from 6 family with total of 357 individual. Data analysis showed species diversity index (H) the highest value on aquatic habitats 0,957 and the lowest on terestrial habitats 0,690. For evenness index (e), the highest value on aquatic habitats 0.835 and the lowest on terestrial habitats 0,76497. And for similarity index between the aquatic and terestrial habitats by S = 0.4% that means 40% both of amphibians species in both habitats are same and 60% are different. Species abundance showed that has the highest value is Meristogenys phaeomerus by 21%. the greatest chance encounter is Meristogenys phaeomerusÂ 2.111 individuals per hour, this species the most lots of encounter on aquatic habitat. Most amphibians that were found more likely to sit and be quiet activities and there are some who speak out and there is also a mating activity that is Meristogenys phaemerus.Keywords: Amphibians, anura, species biversity, Semahung Mountain